A conceptual model of information sharing in e-government services - Yasin, Azman; Ibrahim, Huda; Ahmad, Mazida; Omar, Mazni; Othman, Abdul Rahim (Universiti Teknikal Malaysia, 2018)
As to provide a better delivery of e-government services, guides should be given to support information sharing and integration. Good practices in information sharing among the state government’s agencies should be adopted. In Malaysia, currently, there is insufficient information about the current practices, states or level of maturity, requirements, models adopted in relation to information sharing for the e-services’ implementation among the government agencies. Previous studies in Malaysia have been conducted in relation to critical factors for e-government services and information sharing. These previous studies focused on conceptual framework which need for more efforts in creating an integrative model to guide information sharing for e-government services. The primary aim of this study is to propose information sharing model to support implementation of e-government for Malaysia and Indonesia environment. A theoretical study is conducted to analyze several prominent information sharing models to identify the appropriate information sharing practices in delivering e-government services. Case studies will be applied to explore the current practices and the state of maturity level of information sharing at inter-organizational level among the states. In-depth interviews to public-sector participants will be carried out based on the best practices. Government documents will also be reviewed to learn the agencies’ vision, mission, objectives and others. The findings will be used as a foundation. These outputs are also expected to formulate guidelines and procedure to best guide information sharing framework to support an implementation of e-government services in Malaysia and Indonesia.